An Uncertain Age : The Politics of Manhood in Kenya - Ocobock, Paul, 1980- (Book collections on Project MUSE., 2017)
In twentieth-century Kenya, age and gender powerfully animated relationships and shaped East Africans' contact with emergent global ideas about age and masculinity. Kenyan men and boys came of age achieving their manhood through changing rites of passage and access to new outlets such as town life, crime, anticolonial violence, and nationalism. And as they did, the colonial government appropriated masculinity and maturity as means of statecraft and control. In An Uncertain Age, Paul Ocobock positions age and gender at the heart of everyday life and state building in Kenya. He excavates how the evolving concept of "youth" energized colonial power and the movements against it, exploring the masculinities boys and young men debated and performed as they crisscrossed the colony in search of wages or took the Mau Mau oath. Yet he also considers how British officials' own ideas about masculinity shaped not only young African men's ideas about manhood but the very nature of colonial rule. Book jacket.